The Evaluation of ESP Textbook “Aviation English for ICAO Compliance” From Lectures’ Perspectives at Vietnam Aviation Academy - Truc, Do Thi Thanh; Thu, Nguyen Thi Kieu; Tan, Huynh (VNU Journal of Science: Education Research; Vol 40 No 3, 2024)
The study aims to evaluate the ESP textbook entitled "Aviation English for ICAO Comliance" currently in use at Vietnam Aviation Academy for air traffic controllers. The evaluation is based on teachers' perspectives. To achieve this goal, an evaluation scale has been built to determine the standards of a good quality ESP textbook based on Bardi's scale (2013). The research sample included 15 lecturers from the Department of Foreign Languages at Vietnam Aviation Academy. A questionnaire of 32 closed-ended and one open-ended items was used, and descriptive statistics were performed for the data analysis. The questionnaire covers eight main areas: i) Student’s needs; ii) The learning process; iii) The communication skills and strategies; iv) Grammar; v) Tasks and activities; vi) The authenticity of the texts; vii) The authenticity of tasks; and viii) Learning strategies. The results show that lecturers have a positive evaluation of the textbook in giving it a good rating .